Effect of Physical State of Gelatin-Plasticizer Based Films on to the Occurrence of Maillard Reactions - Matiacevich, S; Riquelme-Hinojosa, N (Elsevier Ltd, 2015)
The aim of this study was to evaluate the occurrence of the Maillard reaction on gelatin-based films (bovine and salmon) in the glassy state, in mixtures with low molecular weight plasticizers (e.g. glycerol, glucose and trehalose) at different storage times. For testing, the gelatin-plasticizer films were stored under glassy conditions (Tg-10°C), previously determined by calorimetric tests. Studies under accelerated conditions (T 蠑 Tg) were also developed. Color, opacity and browning index (Br) were evaluated by computer vision at all storage times. Results showed in samples stored under glassy conditions that the Maillard reaction did not occur, independent of gelatin origin and type of plasticizer. Changes in color stated by opacity and Br were only significant (p < 0.05) in gelatin-glucose systems under accelerated storage conditions. The inhibition of reaction in gelatin films in the glassy state was related to the well-known conditions of low molecular mobility of glassy matrices, but also with the non-Maillard reactive characteristics of glycerol and trehalose. © 2014 Elsevier Ltd. All rights reserved.
Keywords: Bovine gelatin; Salmon gelatin; Plasticizers; Glassy state; Maillard reaction